CONSTRUCTION OF TIPPED OPTICAL FIBER MAGNETIC FIELD SENSOR BASED ON ASI TECHNIQUE - Anwaar A. Al – Dergazly; Alhuda A. Al-Mfrji (Journal of Mechanics of Continua and Mathematical Sciences)
Tipped FBGs are designed to have specific geometrical modifications at their ends, which can enhance their interaction with external stimuli such as magnetic fields. This design can lead to improved sensitivity and specificity in sensing applications. An amplitude splitting interferometer (ASI) with a very sensitive stepping stage allows for precise control over measurements and adjustments during fabrication. This technique is used for achieving high-quality FBGs with minimal defects. The 405 nm laser will be chosen to work in an optimal wavelength range for writing FBGs into photosensitive materials and olive oil, as this wavelength is effective in inducing refractive index changes. The manufactured Tipped FBGs chose the reflected wavelength at 532.1 nm, 0.2 pm/Gauss sensitivity of the sensor.